2018
DOI: 10.1108/ijm-01-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soft skills on French post-secondary graduates’ earnings

Abstract: Purpose The purpose of this paper is to construct soft-skill indicators and measure their effects on graduates’ earnings using survey data from a sample of master’s degree graduates in France. Design/methodology/approach The authors use a quantile analysis to measure the effects of soft skills on income. Findings Certain soft skills explain a proportion of the earnings of recent master’s graduates. In particular, they influence the highest salaries and are important for the most highly skilled jobs. Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
0
16
0
3
Order By: Relevance
“…There is less evidence on the relationship between grit and wages. Albandea and Giret (2018) found positive returns to grit amongst French graduates.…”
Section: Related Literaturementioning
confidence: 94%
“…There is less evidence on the relationship between grit and wages. Albandea and Giret (2018) found positive returns to grit amongst French graduates.…”
Section: Related Literaturementioning
confidence: 94%
“…On the contrary, Deming (2017) focuses on the growth in soft skill demand in the US labor market. Other work on hard vs soft skills includes Pinto and Ramalheira (2017), Deming (2017), Baert and Verhaest (2018) and Albandea and Giret (2018). In an increasingly polarizing labor market, the returns to skills is an important topic.…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have concluded that soft skills have more effect on innovation than hard skills (Ibrahim, Boerhannoeddin & Bakare, 2017;Albandea & Giret, 2018;Viviers, Fouche & Reitsma, 2016;Escrig-Tena et al, 2018). However, this research shows that hard skills have a greater effect on teachers' innovation capability.…”
Section: Discussionmentioning
confidence: 57%